Correctly identifying the cells of origin is essential for tailoring treatment and understanding the emergence of cancer stem cells and late metastases - Waldum, Helge; Slupphaug, Geir (Frontiers in Oncology, 2024)
Malignancy manifests itself by deregulated growth, and the ability to invade surrounding tissues or metastasize to other organs. These properties are due to genetic and/or epigenetic changes, most often mutations. Many aspects of carcinogenesis are known, but the cell of origin has been insufficiently focused on, which is a pity since the regulation of its growth is essential to understand the carcinogenic process and guide treatment. Similarly, the concept of cancer stem cells as cells having the ability to stop proliferation and rest in a state of dormancy and being resistant to cytotoxic drugs before "waking up" and become a highly malignant tumor recurrence, is not understood. Some tumors may recur after decades, a phenomenon probably also connected to cancer stem cells. The present review shows that many of these questions are related to the cell of origin as differentiated cells being long-term stimulated to proliferation.